2014
DOI: 10.1136/bmj.g3175
|View full text |Cite|
|
Sign up to set email alerts
|

Posterior circulation ischaemic stroke

Abstract: Summary pointsPosterior circulation stroke accounts for 20-25% (range 17-40%) of ischaemic strokes Posterior circulation transient ischaemic attacks may include brief or minor brainstem symptoms and are more difficult to diagnose than anterior circulation ischaemia Specialist assessment and administration of intravenous tissue plasminogen activator are delayed in posterior circulation stroke compared with anterior circulation strokeThe risk of recurrent stroke after posterior circulation stroke is at least as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(132 citation statements)
references
References 63 publications
2
111
0
3
Order By: Relevance
“…Posterior circulation ischaemic stroke causes about 20% of ischaemic strokes and affects more than 20 000 people each year in the UK 23. The New England Medical Center Posterior Circulation Registry (NEMC-PCR)4 provides useful demographic data on those experiencing posterior circulation stroke (defined using brain imaging): patients had a mean age of 60.5 years; 63% were men, and approximately a quarter (24%, n=98) had a preceding transient ischaemic attack 4…”
Section: What Is Posterior Circulation Ischaemia?mentioning
confidence: 99%
“…Posterior circulation ischaemic stroke causes about 20% of ischaemic strokes and affects more than 20 000 people each year in the UK 23. The New England Medical Center Posterior Circulation Registry (NEMC-PCR)4 provides useful demographic data on those experiencing posterior circulation stroke (defined using brain imaging): patients had a mean age of 60.5 years; 63% were men, and approximately a quarter (24%, n=98) had a preceding transient ischaemic attack 4…”
Section: What Is Posterior Circulation Ischaemia?mentioning
confidence: 99%
“…Several studies have shown that posterior circulation ischemic stroke (PCS) differs from anterior circulation ischemic stroke in many ways, including stroke mechanisms [2][3][4] . Despite its importance, the amount of studies on PCS is disproportionably fewer than that on anterior circulation ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Conscious change independently predicted mortality at 3 months. Quadriparesis, National Institutes of Health Stroke Arterial dissection (AD) is reported more frequently as the etiology in PCS than in anterior circulation ischemic stroke [2,3,5] . We recently reported that PCS is a heterogeneous disease, and one-fourth of PCS were caused by AD (AD-PCS) [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that sensitivity CT may be approaching 100% if performed in the first 6–12 hours after onset of symptoms of subarachnoid haemorrhage2 and thus lumbar puncture may not be necessary if a serious caution or contraindication exists 3. MR is clearly the investigation of choice in a case such as this, where a patient presents with acute neurological signs suggestive of a potential posterior circulation stroke 4 5. However, MR remains unavailable outside standard working hours in many hospitals 6.…”
Section: Discussionmentioning
confidence: 99%